The Eighth Day and the 49 Year Cycle: Unlocking the Mystery of Numbers in the Ethiopian Orthodox Tewahedo Church - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2026)
The Ethiopian Orthodox Tewahedo Church (EOTC) preserves a rich but largely unstudied tradition of numerical symbolism. This article provides the first systematic analysis of two interconnected numbers at the heart of that tradition: the Eighth Day (number 8) as a symbol of resurrection and new creation, and the 49‑Year Cycle as a framework for sacred time rooted in biblical Jubilee theology. Drawing on patristic sources preserved in Ge’ez, liturgical texts (including anaphoras and the Mawas‘et), the canonical Book of Jubilees, and the distinctive Ge’ez numeral system, the article argues that these two numbers together reveal a coherent theological system – a cruciform temporality in which the 49‑year cycle provides the horizontal structure for sacred time while the Eighth Day introduces the vertical irruption of eternity. This synthesis shapes Ethiopian Orthodox worship, baptismal practice, calendar computation, and eschatological hope. The article also surveys other sacred numbers (3, 7, 12, 13, 40, 318, 777), identifies critical research gaps (lack of primary source engagement, under‑exploration of Ge’ez gematria, conflation of official and popular practice), and proposes an interdisciplinary research agenda. The Ethiopian Orthodox numerical tradition offers a distinctive and underexplored contribution to global Christian theology, deserving of further philological, archaeological, comparative, ethnographic, and computational study.